2010
DOI: 10.1007/s10295-010-0917-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of molecular techniques for identification and enumeration of Raoultella terrigena ATCC 33257 in water purifier efficacy testing

Abstract: Raoultella terrigena ATCC 33257, a representative of the coliform group, is commonly used as a challenge organism in water purifier efficacy testing. In addition to being time consuming, traditional culturing techniques and metabolic identification systems (including automated systems) also fail to accurately differentiate this organism from its closely related neighbors belonging to the Enterobacteriaceae group. Molecular-based techniques, such as real-time quantitative polymerase chain reaction (qPCR) and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Raoultella spp. has been reported to closely related to Enterobacteriaceae group (O'Connell et al, 2010;Saha, Bechanko, Bestervelt, & Donofrio, 2011), and found to be associated with aquatic environment and remarked as a major histamine producers similar to genus Morganella (Dalgaard & Emborg, 2009). In seafood products such as dried milkfish R. ornithinolytica has been isolated and reported to produce more than 800 mg histamine/kg in laboratory media supplement 1% L-histidine (Tsai et al 2007) while R. planticola produced more than 1,000 mg histamine/kg in fresh tuna (Dalgaard & Emborg, 2009).…”
Section: Cell Morphology and Growth Observationmentioning
confidence: 99%
“…Raoultella spp. has been reported to closely related to Enterobacteriaceae group (O'Connell et al, 2010;Saha, Bechanko, Bestervelt, & Donofrio, 2011), and found to be associated with aquatic environment and remarked as a major histamine producers similar to genus Morganella (Dalgaard & Emborg, 2009). In seafood products such as dried milkfish R. ornithinolytica has been isolated and reported to produce more than 800 mg histamine/kg in laboratory media supplement 1% L-histidine (Tsai et al 2007) while R. planticola produced more than 1,000 mg histamine/kg in fresh tuna (Dalgaard & Emborg, 2009).…”
Section: Cell Morphology and Growth Observationmentioning
confidence: 99%